Psychological Perspectives of Scientific Researchers in Studying The Problem of Involvement - Quliyev Yorqin Karimovich (Jurnal Psikologi, 2025)
This article analyzes the phenomenon of involvement as a central link in the relationship between the individual and society. At the same time, the history of the concept of involvement, philosophical and psychological approaches, as well as the involvement of employees of organizations are analyzed. Modern definitions of the phenomenon of involvement, analytical models, and forms of manifestation in work are described based on foreign and national research